The Adoption of Team-Based Learning to Enhance Reading Motivation in the Teaching of Linguistics - KIHEL, Ratiba; BELOUAHEM, Riad (Journal of Human Sciences, 2025)
This study examines the effect of Team-Based learning on enhancing reading motivation in Linguistics for first year students . A Reading Motivation Questionnaire was administered prior the application of team-Based learning and after it in the teaching of Linguistics, to see whether this novel instructional strategy can effectively foster students’ engagement with reading materials. The study included two groups : one experimental with 25 participants and another control with the same number. The findings showed that the majority of students have medium reading motivation, but when applying TBL, there was a significant increase in students’ reading efficiency and there was also a major improvement in their intrinsic motivation, whereas a minor increase in their extrinsic motivation was noticed. The results provide insights for instructors about the triangular and changing nature and shape of reading motivation .that enable them to develop student’s everlasting love for reading linguistic materials.